Validade e reprodutibilidade do COPD assessment test (CAT) em pacientes com bronquiectasia n??o-fibrose c??stica - Castro, Rejane Agnelo Silva de (2015)
Introduction: Instruments to objectively assess the perception of symptoms in patients with BCQ are scarce. Patients with COPD and bronchiectasis (BCQ) share similar symptoms. Therefore, COPD Assesment Test (CAT), originally developed for COPD may be suitable for use in these patients. Objective: To validate and test the reproducibility of the CAT for non-cystic fibrosis (non???CF) bronchiectasis patients. Methods: Hundred patients (FEV1 52 ?? 25%; FVC 67 ?? 22%; 48 ?? 14 years; 42 males) underwent spirometry, cardiopulmonary exercise testing (peak workload and VO2), and shuttle walk test (ST). They answered the Saint George Respiratory Questionnaire (SGRQ) and the Medical Research Council (MRC) scale, and the CAT in two different days (CAT-1 and CAT-2). A pedometer recorded the No. of steps/day (NSD). Results: CAT showed a positive correlation with SGRQ domains (r = 0.74, p< 0.001) and MRC (r = 0.49, p< 0.001). A negative correlation was observed among CAT and lung function (FVC%: r= -0.33, p= 0.001; FEV1%: -0.28, p = 0.004), peak workload (r = -0.31, p = 0.001), VO2 (r = -0.44 p< 0.001), distance walked on ST (%, r= -0.46, p< 0.001), and NSD (r = -0.74, p< 0.001). There was an excellent reliability in the scores from CAT-1 and CAT-2 (21 ???13.25 ??? 26.75??? and (19 ???13 ??? 26.75???, respectively) with high intraclass correlation coefficient (ICC: 0.92 [95% CI: 0.83 ??? 0.96], p< 0.001). Conclusion: CAT is a valid instrument for measuring the impact of bronchiectasis in well-being and daily life of patients with BCT, and is a reproducible questionnaire.